SEED: a tool for disseminating systematic review data into Wikipedia - Schmidt, Lena; Friedel, Johannes; Adams, Clive E. (BioMed Central, 2017)
Wikipedia, the free-content online encyclopaedia, contains many heavily accessed pages relating to healthcare. Cochrane systematic reviews contain much high-grade evidence but dissemination into Wikipedia has been slow. New skills are needed to both translate and relocate data from Cochrane reviews to implant into Wikipedia pages. This letter introduces a programme to greatly simplify the process of disseminating the summary of findings of Cochrane reviews into Wikipedia pages.